2015
DOI: 10.1155/2015/603529
|View full text |Cite|
|
Sign up to set email alerts
|

Silymarin Accelerates Liver Regeneration after Partial Hepatectomy

Abstract: Partial hepatectomy (PHx) is a liver regeneration physiological response induced to maintain homeostasis. Liver regeneration evolved presumably to protect wild animals from catastrophic liver loss caused by toxins or tissue injury. Silymarin (Sm) ability to stimulate liver regeneration has been an object of curiosity for many years. Silymarin has been investigated for use as an antioxidant and anticarcinogen. However, its use as a supportive treatment for liver damage is elusive. In this study, we fed silymari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Silymarin has very strong antioxidant activity which can protect liver from both acute and chronic toxicity and injury (Gillessen et al 2014;Abdel-Moneim et al 2015;Luangchosiri et al 2015;Wu et al 2015). Also, silymarin can suppress various inflammatory responses by suppressing NF-jB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin has very strong antioxidant activity which can protect liver from both acute and chronic toxicity and injury (Gillessen et al 2014;Abdel-Moneim et al 2015;Luangchosiri et al 2015;Wu et al 2015). Also, silymarin can suppress various inflammatory responses by suppressing NF-jB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Liver regeneration evolved presumably to protect wild animals from catastrophic liver loss caused by toxins or tissue injury (Wu et al 2015). Lactulose administration accelerates post hepatectomized liver regeneration in rats by inducing hydrogen, which may result from attenuation of the oxidative stress response and excessive inflammatory response (Yu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…But in case of silymarin, Wu and Tsai et al have stated that silymarin plays a crucial role in accelerated liver regeneration after Partial hepatectomy. It accelerates the cell cycle in the G1 to S phases (Wu et al 2015). In the D r a f t same time Cetinkunar and Tokgoz et al demonstrated that silymarin does not contributed to proliferative regeneration of the liver-which has very important metabolic functions -after partial hepatectomy; instead it will decrease serum levels of transaminases (Cetinkunar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies focused on understanding the liver regeneration and on new pharmacological developments are important. Studies on animals have demonstrated the effect of agents, such as silymarin (2) , bicyclol (3) , curcumin (4) , and amiodarone (5) in increasing regeneration, but thus far, no studies have investigated the effect of dipyridamole on liver regeneration. Cellular cyclic adenosine monophosphate (cAMP) is a secondary messenger, and has an important role in cellular response to ischemia-reperfusion, toxic injury and surgical trauma.…”
Section: Introductionmentioning
confidence: 99%